The Function and Role in the IBAN Social Rank in their Communities - Anak Anggo, Fujica; Laja, Louis (International Journal of Engineering and Technology, 2018)
The Sea Dayaks, better known as the Ibans, inhabit nearly the whole of Sarawak. The Ibans belong to the Proto-Malay groups and historically, they were from the Kapuas Valley in West Kalimantan, Indonesia. They migrated to Sarawak about fifteen generations ago in the mid 16th century (the 1630s). They went to the state through the Kumpang Valley and inhabit Batang Ai and then split to several places in Sarawak (Morgan, 1968). Although the Ibans have a social status in their traditional belief, they do not have a hierarchy of social status such as the Orang Ulu. However, they have elevated the status so-called Pengulu, Tuai Rumah, Tuai Burung, Lemambang, Manang, Beliau, Tukang Sabak, dan Indu Takar. The era of modernization has led to changes to the knowledge of the young generation, especially the younger generation of the Ibans who lack knowledge about the function and role of each rank status in their communities. Therefore, this study was conducted qualitatively through an interview with expert informants, observation, and documentation. This research was hoped to contribute to the general knowledge of the Iban community and other communities in the preservation of the function and role of each social status in the Iban community.Â Â